2017
DOI: 10.1088/1361-6463/aa900f
|View full text |Cite
|
Sign up to set email alerts
|

Zero-group-velocity acoustic waveguides for high-frequency resonators

Abstract: The propagation of the Lamb-like modes along a silicon-on-insulator (SOI)/AlN thin supported structure was theoretically studied in order to exploit the intrinsic zero group velocity (ZGV) features to design electroacoustic resonators that don't require metal strip gratings or suspended edges to confine the acoustic energy. The ZGV resonant conditions in the SOI/AlN composite plate, i.e. the frequencies where the mode group velocity vanishes while the phase velocity remains finite, were investigated in the fre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Theoretically, thickness stretch mode results from multiple reflections of P waves between the top and bottom surfaces of a solid plate. The resonance frequency of the thickness stretch mode is the cut-off frequency of the first symmetric Lamb mode [18]. However, it has been observed that the dominant frequency from the conventional IE test setup is slightly lower than the thickness stretch mode [19,20].…”
Section: Figurementioning
confidence: 99%
“…Theoretically, thickness stretch mode results from multiple reflections of P waves between the top and bottom surfaces of a solid plate. The resonance frequency of the thickness stretch mode is the cut-off frequency of the first symmetric Lamb mode [18]. However, it has been observed that the dominant frequency from the conventional IE test setup is slightly lower than the thickness stretch mode [19,20].…”
Section: Figurementioning
confidence: 99%
“…The behavior of the Si/SiO 2 /ZnO SAW devices operating as gas sensors was studied by 2D FEM with Ansys software, under the hypothesis that the surface of the ZnO layer is covered with a thin polyisobutylene (PIB) film, 0.8 µm thick. The sensor was investigated for the detection of the following five volatile organic compounds at atmospheric pressure and room temperature: dichloromethane (CH 2 Cl 2 ), trichloromethane (CHCl 3 ), carbontetrachloride (CCl 4 ), tetrachloroethylene (C 2 Cl 4 ), and trichloroethylene (C 2 HCl 3 ) [23,24]. The PIB interaction with the gas molecules, i.e., the sensing mechanism, was simulated as an increase in mass density, ρ = ρ unp + ∆ρ, being ρ unp the unperturbed mass density of the PIB layer (in air) and ∆ρ the partial density of the gas molecules adsorbed in the PIB layer, ∆ρ = K•M•c 0 •P/RT, where P and T are the ambient pressure and temperature (1 atm and 25 • C), c 0 is the gas concentration in ppm, K = 101.4821 is the air/PIB partition coefficient for the studied gas, M is the molar mass, and R is the gas constant [24][25][26][27].…”
Section: Gas Sensing Simulationmentioning
confidence: 99%
“…The distinction between symmetric and antisymmetric Lamb modes in Figure 2a,b is somewhat artificial for a composite plate as the symmetry with respect to the mid plane of the plate is lost in the plate under study. Thus the quasi-Lamb mode dispersion curves can be only generically distinguished by a number in the order in which the modes appear along the frequency axis [5]. Some branches of the group velocity dispersion curves, corresponding to the ''backward-wave'' propagation, occur in the negative-slope region where group velocity and phase velocity have opposite signs.…”
Section: Lamb Modes In Diamond/aln Composite Platementioning
confidence: 99%